Evoked potentials in neurocysticercosis - Resende, LAD; Agapejev, S.; Rodrigues, R.; Schelp, A. O. (Assoc Arquivos De Neuro- Psiquiatria, 1997)
In 25 patients with cysticercosis of central nervous system, classified in two clinical forms, benign and malign, evoked potentials were obtained. Normal exam was round in 9 cases with the benign form. From 4 patients with malign clinical presentations, 2 had multiple abnormalities of the evoked potentials, and F wave alterations (mixed pattern). The authors suggest that this mixed pattern may be indicative of severe prognosis.
Keywords: evoked potentials; neurocysticercosis; prognosis